The Development of Interactive Learning Media Using Articulate Storyline 3 on the 'My Indonesia is Rich' Material for the Fifth Grade Students at SDN 07 Sitiung - Anggrayni, M; Susilawati, Wiwik Okta; Ramadani, Anggun Suci (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research was motivated by the limited use of instructional media in the IPAS (Integrated Science and Social Studies) subject. The frequent use of conventional and monotonous media leads to student boredom, lack of engagement, and poor concentration, ultimately affecting learning outcomes. To overcome this problem, this study developed interactive learning media using Articulate Storyline 3 on the topic